(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study investigates educational outcomes, personality traits, nutritional status, and adjustment levels among primary school students from government and non-government schools across India, with a focus on Uttar Pradesh. Employing standardized instruments, the research assesses academic performance, personality dimensions using the Big Five model, nutritional assessments, and emotional and social adjustment in a diverse sample of 400 students. Preliminary findings indicate significant disparities in educational achievement and nutritional health, with students from non-government schools generally outperforming and reporting better nutritional status than those from government schools. Moreover, students at non-government schools displayed higher levels of conscientiousness and social adjustment